Ecology of a population of oribi Ourebia Ourebi Ourebi (Zimmerman, 1783) in the Golden Gate Highlands National Park - Bothma, Jacobus du P. (University of Pretoria, 2022)
Dissertation (MSc (Wildlife Management))--University of Pretoria, 1989.